Ilmenite ore as an oxygen carrier for pressurized chemical looping reforming: Characterization and process simulation. (February 2019) - Symonds, Robert T.; Sun, Zhenkun; Ashrafi, Omid; Navarri, Philippe; Lu, Dennis Y.; Hughes, Robin W.
Highlights: PCLR appears to be a promising option for the production of diluent at SAGD facilities. Partial reduction of ilmenite ore to Fe2.5+ and Fe2+ containing species is required to avoid the production of CO2. Steam and diluent requirements can be met, with excess power generation, at lower costs than traditional syngas technologies. CO2 emissions targets can be met, while reducing boiler feed water (BFW) make-up. Abstract: Chemical looping reforming is a promising option for the conversion of gaseous fuels to high quality syngas suitable for gas-to-liquids (GtL) processes. This work evaluates the potential for syngas, heat, power, and steam generation for diluent production at steam assisted gravity drainage (SAGD) facilities using low cost ilmenite ore pressurized chemical looping reforming (PCLR). Preliminary fixed-bed reactor testing on a naturally occurring Canadian ilmenite ore was performed to determine the optimal operating regime for syngas generation. Based on SEM characterization, EDX elemental mapping, XRD, and Mössbauer spectroscopy measurements it was demonstrated that partial reduction to Fe 2.5+ and Fe 2+ containing species is required to avoid the production of CO2 . Additionally, the reduction to Fe° containing species should be minimized to limit the formation of carbon and metal carbides. These results were used to generate material and energy balances via Aspen HYSYS V9 process simulation software of the entire PCLR process for SAGD applications using a Canada's Oil Sands Innovation Alliance (COSIA) SAGD facility template. Thorough energy integration of the combined PCLR-SAGD process using Pinch Analysis suggests that steam and diluent requirements can be met, with excess power generation, at lower costs than more traditional syngas generation technologies, while meeting CO2 emissions targets and reducing boiler feed water (BFW) make-up. Having shown that process performance is attractive, a techno-economic assessment to establish the most economical design for the PCLR-SAGD process is now required.